Preliminary Survey on The Termite Mounds, Their Interior Geometrics and The Termite Prevention from Infrastructural Construction at New Site of Ndola International Airport in Zambia - M. Sichilima, Alfred; Qinglin, Kong; Zhang, Lei; K Mumba, Ngandwe; Shen, Jiejie; Li, Jianzhong; Samuel, Boby (Journal of Plant and Animal Ecology, 2018)
An ecological study was conducted on termites located at the new site of Ndola International Airport in Zambia. The aim of this study was: (a) to assess the distribution pattern of different sizes of termite mounds located at the site, (b) to investigate the interior geometrics of termite mounds, (c) to determine the colony sizes of termites per each mound found at the site and (d) to provide technical expertise on the different termite preventive methods used on new buildings. Methods Using an aero-drone fitted with a camera, aerial surveys were conducted to capture and evaluate the spread of differently sized mounds at the site. Mathematical models were used to calculate the volume and number of nests contained in each mound. The colony sizes were captured and recorded per each mound. Analysis Multivariate statistical analyses were performed using SPSS, to compute a two way ANOVA table for comparison of p-values involving the colony sizes and the volumes of nests for small and big mounds. The ratios affecting these volumes were also calculated. Results The total of 1,880 termite mounds was captured spreading at an average of 14 mounds/ 1km2. Results further showed that 65% of total mounds were actively housing termites while 32% were virtually deserted. The 3% balance of mounds were occupied by rodents, ants and snakes, respectively. Progression on the volume of nests in bigger and smaller mounds, significantly tallied with the size of mound at p < 0.0121 and p < 0.0346, respectively. Similarly, the colony size of termites in small and larger mounds was also significant at p < 0.002 and p < 0.001, respectively. The nest volume ratios of small, medium and larger mounds were also markedly increasing with the size of mound at 1:8.7-small, 1:32.8 medium and 1:1, 098.6-large, respectively. Conclusion Not every existing termite mound is occupied by termites; the size of nest was directly related to the size of mound; the size of colony concurrently increased with that of the volume of nest. This study unravels some intriguing and conflicting suggestions that smaller mounds can still have larger colonies underground and vice versa. Furthermore, this study is the first in Zambia to combine the concepts of termite habitat geometrics and infrastructural protection.
Keywords: Termite Mounds; Termites; Colony Size; Termite Prevention; Aerial Survey; Zambia